Ethical value conflicts in healthcare and their effects on nurses’ health, turnover intent, team effectiveness, and patient safety: a longitudinal questionnaire study - Larsman, Pernilla; Pousette, Anders; Skyvell Nilsson, Maria; Gadolin, Christian; Törner, Marianne (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVE ': 'Moral distress emanating from value conflicts comprising ethical dimensions pose a threat to nurses’ health and retention, as well as to the quality of care. The aim of the present study was to investigate the relationships between the frequency of ethical value conflicts (EVC), and the perceived distress when they occur, respectively, and nurses’ work-related stress, burnout symptoms, turnover intent, team effectiveness, and patient safety. ' ' METHODS ': 'A two-wave longitudinal cohort questionnaire study was performed among registered nurses at six hospitals in two Swedish regions. Cross-sectional analyses (T1) were based on 1817 nurses in 228 care units (CU), and longitudinal analyses (T1 – T2) on 965 nurses in 190 CU. Hypothesis testing was performed using multilevel controlled regression modeling. ' ' RESULTS ': 'The results indicated that nurses who were often exposed to EVC also to a higher extent tended to report these conflicts as stressful. Frequent exposure to EVC induced by insufficient resources, inapt organizational structures or interpersonal staff relations were cross-sectionally associated with work-related stress, burnout symptoms, turnover intent, and team effectiveness. The longitudinal analyses indicated that EVC induced by a lack of resources primarily had negative effects on nurses’ health and well-being. At the CU level, such conflicts also impaired team effectiveness. At the individual level, EVC induced by organizational constraints or interpersonal relations negatively affected care effectiveness. ' ' CONCLUSIONS ': 'EVC are related to negative consequences in healthcare, and such processes take place both on the individual and organizational levels.
Keywords: ethical dilemma; ethical value conflict; healthcare; longitudinal questionnaire; moral distress; nurse; nurses' health; nurses’ well-being; nursing; patient safety; quality of care; team effectiveness; turnover